ANALISIS FAKTOR PSIKOLOGIS KONSUMEN DAN PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN - Wasis A. Latif (Fakultas Ilmu Administrasi Universitas Brawijaya (FIA UB))
In addition, manufacturer and marketer of handphone Qwerty must maintenance the performance and quality products for self-assessment in the consumer, that by buying a handphone Qwerty in accordance with quality and has a function for the good. In addition, manufacturers must maintain performance handphone  Qwerty and the quality of its products to arise in consumer confidence that has made a proper assessment to buy handphone Qwerty. In addition, handphone manufacturers Qwerty always maintain and continuously improve product quality and variety of other supporting factors, such as by providing authorized service center, after-sales service, parts availability, and not to leave the campaign by promoting the benefits of handphone Qwerty compared with other mobile phone, given the increasingly diverse and many competitors in the telecommunications industry.   Keywords : consumer self-assessment, consumer psychology, quality products, telecommunications industry